2018
DOI: 10.5254/rct-18-82632
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Specific Surface Area of Highly Dispersible Silica and Interfacial Characteristics of Green Elastomer Composites

Abstract: Epoxidized natural rubber (ENR) is a modified form of NR bearing polar epoxy groups. The focus is on dispersion of highly dispersible silica (HDS) filler with three different specific surface areas in ENR 25/ENR 50 composites. The effect of three different specific surface areas of HDS on bound rubber content, Payne effect, physicomechanical properties, and viscoelastic properties of the green composites was studied in detail. Also, the influences of epoxide content in ENRs in the absence of silane coupling ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…[14][15][16]. Besides these studies, many material developments for a better silica dispersion, such as the modification of polymers, silica, and silanes, are going on [17][18][19][20][21]. Overall, these studies primarily indicate that the silanization reaction plays a pivotal role for the dispersion and the bound rubber formation of a silica-filled rubber [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16]. Besides these studies, many material developments for a better silica dispersion, such as the modification of polymers, silica, and silanes, are going on [17][18][19][20][21]. Overall, these studies primarily indicate that the silanization reaction plays a pivotal role for the dispersion and the bound rubber formation of a silica-filled rubber [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…According to investigations, higher surface area of silica resulted to an increased reinforcing effect due to strong polymer-filler while decreasing filler-filler interactions [163]. In addition, the large surface area of bamboo charcoal (BC) particles improved the stress transfer properties between PLA to BC enhanced strength and ductility index of the PLA-BC composite [164].…”
Section: Specific Surface Areamentioning
confidence: 99%
“…Down the lane, researchers had been working to develop green technologies in tyre manufacturing to obtain a balance between rolling resistance and road grip. To reduce the rolling resistance, modifications can be made to the rubber compound, tread design and tyre build [ 22 ]. Accordingly, the viscoelastic properties (mainly loss factor) of the rubber compound were modified by the usage of silica fillers, other nanomaterials and steps taken to improve the filler dispersion in the compound, improvised the crosslinking process and also increased the usage of natural rubber [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the rolling resistance, modifications can be made to the rubber compound, tread design and tyre build [ 22 ]. Accordingly, the viscoelastic properties (mainly loss factor) of the rubber compound were modified by the usage of silica fillers, other nanomaterials and steps taken to improve the filler dispersion in the compound, improvised the crosslinking process and also increased the usage of natural rubber [ 22 ]. It was found that tread contributed to more than 60% of the total tyre losses and hence changes were also introduced in the tread design by providing nano coatings to tread, reducing the depth of the tread pattern and introducing 3D shaping technology.…”
Section: Introductionmentioning
confidence: 99%